Peran Sinematografi dalam Indoktrinasi pada Film Midsommar - Ibrahim, Mahesa (Fakultas Desain Universitas Komputer Indonesia, 2023)
The movie of Midsommar (2019) tells a story about a grief-stricken and lonely young woman, Dani Ardor, who was horrified by the sadistic tradition of The Hårga but eventually becomes part of the commune. It is a fairy tale where at some point the Big Bad Wolf convinced Little Red Riding Hood that happily-ever-after can be found in his sharp teeth. This movie is often classified as “elevated horror”, “folk horror”, and even a sadistic breakup movie. At the same time, this movie is also tells a story about indoctrination carried by a group whose strategy is also used by the writer-director, Ari Aster, in brainwashing the audience both through the characterization of Dani Ardor and the cinematography techniques. The purpose of this research is to find out the role of cinematography in indoctrinating the character of Dani and the audience in the film Midsommar (2019) so that it can be known what aspects influence it.